Investigating the Relationship Between Hopelessness, Alexithymia, Mind Wandering, Rumination, and Clinical Features in Patients with Bipolar Disorder - Andrea Aguglia; Tommaso Cerisola; Martina Rimondotto; Simona Iannini; Francesco Bruni; Francesca Bigiotti; Alessandra Costanza; Mario Amore; Andrea Amerio; Gianluca Serafini (Brain Sciences)
Background/Objectives: The understanding of the mechanisms involved in the etiopathogenesis and maintenance of Bipolar Disorder (BD) should be a priority to identify potential early clinical markers that could help in improving treatment strategies and prevention. The aim of this study was to investigate the potential correlation between hopelessness, alexithymia, mind wandering, and rumination in patients with a primary diagnosis of BD, evaluating whether these psychopathological aspects could negatively affect bipolar illness. Methods: A semi-structured interview was used to collect sociodemographic and clinical characteristics. Several psychometric tools were administered: the Beck Hopelessness Scale; Toronto Alexithymia Scale; Rumination Response Scale; Mind Wandering Questionnaire; Mind Wandering: Deliberate; Mind Wandering: Spontaneous; and the Daydreaming Frequency Scale. Results: Patients with high levels of hopelessness have a greater number of psychiatric and medical comorbidities and are more frequently on polypharmacotherapy. Additionally, patients with high levels of hopelessness show a greater likelihood of having attempted suicide during their lifetime. The presence of alexithymia is associated with longer hospitalization and psychiatric comorbidities. Higher levels of rumination correlate with a greater number of psychiatric and medical comorbidities, and with the presence of residual symptoms. Mind wandering is associated with the presence of medical comorbidities and residual symptoms. Conclusions: Hopelessness, alexithymia, mind wandering, and rumination should be identified as important proxies of impaired subjective well-being that should be carefully monitored because they could further worsen the clinical course of BD and suicidal risk in this vulnerable population.